2017
DOI: 10.1007/s11695-017-2714-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sleeve Gastrectomy on Serum 12α-Hydroxylated Bile Acids in a Diabetic Rat Model

Abstract: The percentage of 12α-hydroxylated bile acids was reduced after SG, which was relevant with the inhibition of CYP8B1 and overexpression of MAFG. These outcomes may play an important role in the improvement of insulin sensitivity following SG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Recent studies have confirmed that MAFG is a target of FXR and a key transcriptional repressor of bile acid synthesis and metabolism [811]. MAFG has been shown to reduce the transcription level of CYP8B1 in the liver [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed that MAFG is a target of FXR and a key transcriptional repressor of bile acid synthesis and metabolism [811]. MAFG has been shown to reduce the transcription level of CYP8B1 in the liver [12].…”
Section: Introductionmentioning
confidence: 99%
“…Serum BA levels were higher in obese patients who received RYGB when compared to controls (no RYGB), and elevated levels of BAs were sustained for at least 2 years post-surgery (Nakatani et al, 2009;Patti et al, 2009). Further investigation demonstrated that the mechanism is due to the regulation of specific BAs (Wang et al, 2017;Browning et al, 2019). This might also be explained by the evidence that plasma BAs were negatively correlated with cognitive restraint of eating (Prinz et al, 2015).…”
Section: Obesitymentioning
confidence: 93%
“…Genetic ablation of Cyp8b1 decreases BA profile hydrophobicity and protects against several metabolic diseases, including obesity and T2D, in mice (Zaborska and Cummings, 2018). Of note, the percentage of 12α-hydroxylated BAs was reduced after SG, associated with overexpression of V-Maf avian musculoaponeurotic fibrosarcoma oncogene homolog G (MAFG) and lower mRNA and protein levels of CYP8B1 (Wang et al, 2017). Interestingly, MAFG is an FXR target gene that transcriptionally represses CYP8B1 expression (de Aguiar Vallim et al, 2015); these results suggest that in addition to FXR and TGR5, the downstream CYP8B1 may present an alternative target for bariatric surgery.…”
Section: Bariatric Surgeriesmentioning
confidence: 99%
“…However, BA includes more than 20 components, each of which may have specific effects on metabolism (de Aguiar Vallim et al, 2013). Notably, 12α-hydroxylated bile acids promote liver fibrosis through TGR5mediated p38MAPK and ERK1/2 signaling, but these bile acids were significantly reduced after SG (Wang et al, 2017;Xie et al, 2021). RYGB upregulates the expression of hepatic BA targets FXR and peroxisome proliferator-activated receptor-α (PPARα) in severely obese patients, and these changes are accompanied by regression of NASH and T2DM after 1 year (Francque et al, 2015;Mazzini et al, 2019).…”
Section: Changes In Bile Acid Metabolism Transport and Signal Transdu...mentioning
confidence: 99%